Anaplastic Thyroid Carcinoma: A ceRNA Analysis Pointed to a Crosstalk between SOX2, TP53, and microRNA Biogenesis - Walter Arancio; Valeria Carina; Giuseppe Pizzolanti; Laura Tomasello; Maria Pitrone; Concetta Baiamonte; Marco Calogero Amato; Carla Giordano (International Journal of Endocrinology)
It has been suggested that cancer stem cells (CSC) may play a central role in oncogenesis, especially in undifferentiated tumours. Anaplastic thyroid carcinoma (ATC) has characteristics suggestive of a tumour enriched in CSC. Previous studies suggested that the stem cell factor SOX2 has a preeminent hierarchical role in determining the characteristics of stem cells in SW1736 ATC cell line. In detail, silencing SOX2 in SW1736 is able to suppress the expression of the stem markers analysed, strongly sensitizing the line to treatment with chemotherapeutic agents. Therefore, in order to further investigate the role of SOX2 in ATC, a competing endogenous RNA (ceRNA) analysis was conducted in order to isolate new functional partners of SOX2. Among the interactors, of particular interest are genes involved in the biogenesis of miRNAs (DICER1, RNASEN, and EIF2C2), in the control cell cycle (TP53, CCND1), and in mitochondrial activity (COX8A). The data suggest that stemness, microRNA biogenesis and functions, p53 regulatory network, cyclin D1, and cell cycle control, together with mitochondrial activity, might be coregulated.